PENGARUH PENERAPAN METODE PEMBELAJARAN MNEMONIK BERBASIS MEDIA MINI BOOK TERHADAP KEMAMPUAN DAYA INGAT PESERTA DIDIK PADA MATA PELAJARAN IPS DI KELAS VIII SMP RAUDLATUL MUTA’ALLIMIN - Lathifatus Suniyyah; Asnimawati Asnimawati; Ali Imron; Nurul Hasanah (STKIP Subang, 2026)
Memory retention is a crucial aspect of Social Studies (IPS) learning, particularly regarding historical material that encompasses numerous facts, figures, and interconnected sequences of events. Preliminary observations in a Grade VIII class at SMP Raudlatul Muta'allimin revealed that only 28.9% of students achieved scores above the Minimum Mastery Criteria (KKM); students tended to memorize material by rote without employing meaningful encoding strategies. This study aimed to analyze the impact of a mnemonic learning method utilizing